2011
DOI: 10.4103/0973-6131.85486
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an integrated approach of yoga therapy on quality of life in osteoarthritis of the knee joint: A randomized control study

Abstract: Aim:This study was designed to evaluate the efficacy of addition of integrated yoga therapy to therapeutic exercises in osteoarthritis (OA) of knee joints.Materials and Methods:This was a prospective randomized active control trial. A total of t participants with OA of knee joints between 35 and 80 years (yoga, 59.56 ± 9.54 and control, 59.42 ± 10.66) from the outpatient department of Dr. John's Orthopedic Center, Bengaluru, were randomly assigned to receive yoga or physiotherapy exercises after transcutaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 27 publications
1
42
0
1
Order By: Relevance
“…There was limited evidence with medium effect favouring the experimental group that an integrated approach of yoga, transcutaneous electrical stimulation and ultrasound compared with exercise therapy, transcutaneous electrical stimulation and ultrasound (SMD=0.65, CI 0.40 to 0.90)46 was superior in improving QoL in individuals with knee OA (figure 6). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There was limited evidence with medium effect favouring the experimental group that an integrated approach of yoga, transcutaneous electrical stimulation and ultrasound compared with exercise therapy, transcutaneous electrical stimulation and ultrasound (SMD=0.65, CI 0.40 to 0.90)46 was superior in improving QoL in individuals with knee OA (figure 6). …”
Section: Resultsmentioning
confidence: 99%
“…There was limited evidence that (1) moxibustion treatment compared with placebo (SMD=0.09, CI −0.24 to 0.43)52; (2) short-term monochromatic infrared energy compared with placebo (SMD=−0.09, CI −0.55 to 0.37)47; (3) methylsulfonylmethane supplementation compared with placebo (SMD=0.42, CI −0.14 to 0.98)44; (4) Tai Chi Qigong compared with no treatment (SMD=0.46, CI −0.17 to 1.09)49; and (5) enzymatic hydrolysed collagen compared with glucosamine sulfate (SMD=0.12, CI −0.28 to 0.53)55 were as effective in improving QoL of individuals with knee OA (figure 6). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Zainab S Motorwala et al studied the effects of yogasanas on osteoporosis in postmenopausal women and demonstrated that a statistically significant difference was found in the Bone mineral density (BMD ) score. Thus, they concluded that integrated yoga is a safe mode of physical activity which includes weightbearing as well as non-weightbearing asanas, pranayama, and suryanamaskar, all of which helps induce improvement in BMD in postmenopausal osteoporotic females.…”
Section: Discussionmentioning
confidence: 99%